EVALUATION OF HEARING SCHOLARSHIPS LINKED TO AN EXTENSION PROJECT DEVELOPED AT HEARING ON HEALTH IN THE CITY OF MACAÉ, RIO DE JANEIRO. (Fiep Bulletin - online, 2016)
Audiometry is a method that evaluates the ability of human hearing sounds. For some young adults who have never performed the test and do not have information about your hearing health, audiometry shows a single examination, with a difference in the lives of these individuals. This study aimed to describe the hearing ability of scholars linked to an extension project on hearing loss developed in the city of Macae - Rio de Janeiro. We conducted a descriptive, quantitative and primary basis with scholars attached to the project “PET Redes Saudi”, developed in the city of Macaé, RJ. Scholarships holders were individually evaluated by the governess project in outpatient speech therapy Municipal Rehabilitation Center/Semusa - Macaé, for audiometric evaluation. The variables collected were: Age (years), hearing complaints, prior meatoscopy; pure tone audiometry; speech recognition threshold and percentage index speech recognition. Data were entered, consolidated and analyzed by relative frequency, measures of central tendency, using Microsoft Excel 2010 software. A total of 12 scholarship holders and three volunteers (n=15) were evaluated, with a mean age (±SD) 21.8±3.08 years. Was detected in 20% of participants reporting hearing complaints (the first complaining of ear fullness in the left ear, the second complaining of tinnitus and dizziness, and was referred to the otorhinolaringologist). As the result of otoscopy, 10% had alterations. We conclude that all audiometric met the threshold of normality, despite being observed hearing complaints by some scholarship holders evaluated. This experience has provided knowledge and awareness of the students about the need for this examination in the general population.
Keywords: Hearing; Deafness; Hearing Loss.